Dampak Pelatihan dan Etos Kerja terhadap Produktivitas Karyawan di PT XYZ - Mukhamad Ali Safii; Shasha Bedys Fazhiera (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to analyze the impact of training and work ethic on employee productivity at PT XYZ. Training is one of the important factors in improving employee capabilities, while work ethic reflects the attitude and dedication of employees to their work. This research uses a quantitative method with a survey design, where data is collected through questionnaires distributed to employees of PT XYZ. The results showed that effective training and high work ethic have a significant positive impact on employee productivity. The findings are expected to provide recommendations for the management of PT XYZ in designing more effective training programs and encouraging good work ethic among employees.